Pendampingan Belajar Matematika Untuk Anak Usia Sekolah Selama Masa Pandemi Covid 19 - Eka Susilowati (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
The Covis 19 virus that hit in 2019 yesterday left a big impact in various fields, especially the world of Education. The learning process that was previously carried out in offline learning, at that time had to be transferred to online learning. At the time of this community service activity, learning activities were carried out in blended learning schools, namely online and offline. However, many school-age children still adjust to the two learning processes. In the online learning process there are obstacles that they must face. First, for underprivileged families, they find it difficult to participate in learning because they do not have a cellphone or an adequate internet network so that learning cannot be carried out properly. In addition, many school-age children complain about their lack of understanding when learning online, especially Mathematics. They complain that when online, a lot of material is conveyed at a glance and lacks depth.